Altered Histone Mark Deposition and DNA Methylation at Homeobox Genes in Human Oral Squamous Cell Carcinoma. Issue 10 (October 2014) - Marcinkiewicz, Katarzyna M.; Gudas, Lorraine J.
<x xml:space="preserve">Abstract</x> We recently reported a role of polycomb repressive complex 2 (PRC2) and PRC2 trimethylation of histone 3 lysine 27 (H3K27me3) in the regulation of homeobox (HOX) (Marcinkiewicz and Gudas, 2013, Exp Cell Res) gene transcript levels in human oral keratinocytes (OKF6‐TERT1R) and tongue squamous cell carcinoma (SCC) cells. Here, we assessed both the levels of various histone modifications at a subset of homeobox genes and genome wide DNA methylation patterns in OKF6‐TERT1R and SCC‐9 cells by using ERRBS (enhanced reduced representation bisulfite sequencing). We detected the H3K9me3 mark at HOXB7, HOXC10, HOXC13, and HOXD8 at levels higher in OKF6‐TERT1R than in SCC‐9 cells; at IRX1 and SIX2 the H3K9me3 levels were conversely higher in SCC‐9 than in OKF6‐TERT1R. The H3K79me3 mark was detectable only at IRX1 in OKF6‐TERT1R and at IRX4 in SCC‐9 cells. The levels of H3K4me3 and H3K36me3 marks correlate with the transcript levels of the assessed homeobox genes in both OKF6‐TERT1R and SCC‐9. We detected generally lower CpG methylation levels on DNA in SCC‐9 cells at annotated genomic regions which were differentially methylated between OKF6‐TERT1R and SCC‐9 cells; however, some genomic regions, including the HOX gene clusters, showed DNA methylation at higher levels in SCC‐9 than OKF6‐TERT1R. Thus, both altered histone modification patterns and changes in DNA methylation are associated with dysregulation of homeobox gene expression in human oral cavity SCC cells, and this dysregulation potentially plays a role in the neoplastic phenotype of oral keratinocytes. J. Cell. Physiol. 229: 1405–1416, 2014. © 2014 Wiley Periodicals, Inc.